The Legal Politics of Indigenous Peoples’ Rights Recognition Following Constitutional Court Decision Number 35/PUU-X/2012 from a Human Rights Perspective - Frans Tory Damara Pradipta (Punggawa Legacy Center, 2026)
The recognition of indigenous peoples’ rights remains a crucial legal issue in Indonesia despite constitutional guarantees and Constitutional Court Decision Number 35/PUU-X/2012. This study aims to analyze the legal politics of indigenous peoples’ rights recognition following the decision from a human rights perspective. The research employed normative legal research using statutory, conceptual, and case approaches. Legal materials were collected through library research and analyzed qualitatively through legal interpretation and legal reasoning. The findings reveal that Constitutional Court Decision Number 35/PUU-X/2012 strengthened the constitutional position of indigenous peoples by affirming that customary forests are no longer part of state forests. However, the implementation of indigenous rights recognition continues to face challenges, including administrative barriers, regulatory fragmentation, and the absence of comprehensive legislation. From a human rights perspective, these challenges indicate a gap between constitutional recognition and substantive rights protection. Therefore, legal harmonization and institutional reforms are necessary to ensure the effective realization of indigenous peoples’ constitutional and human rights in Indonesia.